PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH DALAM MANAJEMEN PEMASARAN BANK SYARIAH - Azzahra, Fathia Afra Annisa; Fasa, Muhammad Iqbal; Suharto, Suharto (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2025)
This study aims to determine the quality of service in the marketing management of Islamic banks, the most important criteria that can affect customer satisfaction and analyze the level of customer satisfaction in each Islamic bank. This research uses quantitative and secondary methods. With the results of this study can be proven because there is a positive influence on the quality of service to be of interest to customers. From the quality of service, there is also a positive impact on the decision to the customer. From this research, many also found that the equipment for financing includes those that can have a positive impact on becoming customers. Meanwhile, interest in customers will have a positive impact on customer decisions in the quality of Islamic banking services